DIRECTIONS OF COLLECTING EVIDENCE IN AUDITS OF ENTERPRISES PROCESSING GRAIN PRODUCTS (World Economics and Finance Bulletin, 2025)
This article studies the issues of improving the methodology for collecting audit evidence at grain processing enterprises from a scientific, theoretical and practical perspective. In the course of the research, the nature, types of audit evidence, and the requirements of international auditing standards for their sufficiency and relevance were studied. The sectoral characteristics of the grain processing process, the multi-stage nature of the raw material movement, and the complexity of the calculation of technological losses were analyzed from the point of view of their impact on the process of collecting audit evidence
Keywords: grain processing enterprises; audit; audit evidence; analytical procedures